FORMULATION AND EVALUATION OF AMPHOTERICIN B AND MILTEFOSINE COMBINATION NANOVESICLES - BEZABEH, MULUGETA F.; WERBOVETZ, KARL A.; MURTHY, K. V. RAMANA (International Journal of Applied Pharmaceutics, 2021)
Objective: The aim of the present investigation is to formulate and evaluate amphotericin B-miltefosine combination nanovesicles for application in the treatment of visceral leishmaniasis. Methods: Amphotericin B-miltefosine combination (AmB-MTF) nanovesicles were prepared by ethanol injection method. Formulations of nanovesicles were evaluated at varying conditions of lipids composition, drug-lipid proportion, ethanol-water composition and stirring rate, on drug entrapment efficiency and particle size. Results: The study showed that entrapment efficiency was significantly affected (p<0.01) by the effects of lipids composition, drug-lipid proportion, ethanol-water composition, and stirring rate. Particle size of nanovesicles was significantly affected (p<0.05) by drug-lipid proportion and stirring rate. An optimized formulation of amphotericin B-miltefosine nanovesicles was prepared at optimal factors composition of: phosphatidylcholine-cholesterol-stearic acid 20:4:1, drug-lipid 1:8, AmB-MTF 1:1; ethanol-water 1:4 ratios, and stirring rate 1000 rpm. The AmB-MTF 1:1 nanovesicles formulation showed particle size of 145.6 nm, poly dispersity index 0.19, zeta potential-27.3 mV and drug entrapment efficiency 87%. Conclusion: Evaluation of AmB-MTF 1:1 nanovesicles showed development of a successful formulation with very good compatibility, extended drug release, convenient vesicle size and high drug entrapment efficiency. To conclude, AmB-MTF 1:1 nanovesicles formulation could be a safe and reliable therapeutic option over the conventional combination therapy provided further antileishmanial investigations are investigated in vitro and in vivo